Estudio de la adherencia de un sistema compuesto FRCM sostenible para el reforzamiento de elementos de concreto armado. - Almache Hernnández, Jazmín Carolina (2016)
A reinforced concrete structure is analyzed and designed to complete its service life with suitable operating conditions and resistance. In a civil work, however there may be circumstances that generate changes during design, implementation or during its lifetime, and adversely affect its bearing capacity, which could eventually lead to collapse. In this regard, it is often necessary to repair a reinforced concrete structure by using strengthening systems applied on specific structural elements or in the entire structure in order to increase their loading capacity and recover their functionality. One of these systems is commonly called composites materials. The FRCM (Fabric reinforced cementitious matrix) composites are a new development in cement composites specifically designed for structural repair and rehabilitation. There are few studies and limited information regarding the FRCM systems, especially if applications using natural fibers are treated. Given the limited information, studies involving the total of the mechanical properties of these novel strengthening systems have not been conducted. One of the main mechanical properties of composites is adhesion between the matrix and the substrate material. Although a composite system has excellent mechanical properties, if adequate adhesion is not ensured, the strengthening system efficiency is affected. This thesis deals with the development of a FRCM composite system produced with fabrics made from natural fibers of cabuya and a cementitious matrix, focusing on adherence problems and proposing an optimal system to ensure an effective bond between the composite and the substrate material. An extensive research on both the physical and mechanical properties of the materials used in the preparation of the FRCM system (cementitious matrix and fabrics of cabuya) and the preparation of reinforced concrete elements (beams and columns eccentrically loaded) was conducted in the laboratories of Civil Engineering of the National University of Chimborazo.